STRUKTUR PASAR INDUSTRI PERBANKAN INDONESIA: ROSSE-PANZAR TEST - Moh Athoillah (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2010)
The purpose of this research is to determine how the market structure of banking industry in Indonesia. The research using Rosse-Panzar Test (PR) methods. Using panel data of 10 banks in Indonesia which has the largest asset ratings, this PRapproach will produce H-Stat value which is the sum of three main coefficients ofbanking inputs (labor, capital and funds). With H-Stat valued at 0.931 can be con-cluded that the Indonesian banking industry into the category of monopolistic mar-ket.